SPORTS ORIENTATION DURING LEARNING TEAM OR INDIVIDUAL SPORTS USING A SPORT EDUCATION MODEL - Agi Ginanjar; Adang Suherman; Tite Juliantine; Yusuf Hidayat (LPMPP Universitas Negeri Yogyakarta, 2019)
Since competition activities can improve sportsmanship, moral development, motivation, and prepare students in the